Diversification of Bacillus subtilis during experimental evolution on Arabidopsis thaliana and the complementarity in root colonization of evolved subpopulations. (2nd August 2021) - Blake, Christopher; Nordgaard, Mathilde; Maróti, Gergely; Kovács, Ákos T.
Summary: The soil bacterium Bacillus subtilis is known to suppress pathogens as well as promote plant growth. However, in order to fully exploit the potential as natural fertilizer, we need a better understanding of the interactions between B. subtilis and plants. Here, B. subtilis was examined for root colonization through experimental evolution on Arabidopsis thaliana . The populations evolved rapidly, improved in root colonization and diversified into three distinct morphotypes. In order to better understand the adaptation that had taken place, single evolved isolates from the final transfer were randomly selected for further characterization, revealing changes in growth and pellicle formation in medium supplemented with plant polysaccharides. Intriguingly, certain evolved isolates showed improved root colonization only on the plant species they evolved on, but not on another plant species, namely tomato, suggesting A. thaliana specific adaption paths. Finally, the mix performed better than the sum of its constituents in monoculture, which was demonstrated to be caused by complementarity effects. Our results suggest that genetic diversification occurs in an ecological relevant setting on plant roots and proves to be a stable strategy for root colonization.